Challenges in disability certification in psychiatry in India - Apoorva K. Bachhav; Harshit B. Sharma; Kartik M. Singhai (Indian Journal of Psychiatry)
This viewpoint draws attention to the disparities that exist between the Rights of Persons with Disabilities Act, 2016 and the facilities that are available to specialists on the digital platform of certification for mental illnesses to address the severity of the impairment. It also recognizes that the lack of clear rules makes it difficult to reevaluate both single and multiple disabilities. The process of disability certification is further complicated by other factors, including inadequate training of medical professionals and clerical staff, server associated delays as well as the lack of uniformity of standard operating procedures among disability centers across the country.